Implementing Religious Moderation in Digital Space: Challenges and Opportunities Z Generation - Mochammad Rizal Ramadhan; Abdul Basid; Nur Faizin (Aqlamuna: Journal of Educational Studies, 2023)
This article reviews the challenges and opportunities of Z Generation in implementing religious moderation in the digital space. Z Generation is characterized as an open and tolerant generation. Even though it has many negative influences, digital space also has a positive influence on society, especially Generation Z as digital natives in spreading religious moderation. This study used an online survey method for Z generation combined with library research. This discussion examines the many challenges of Z generation in the digital space regarding deviations from religion and opportunities in spreading religious moderation. Given the growing development of extreme/radical group movements in the digital space, to maintain the stability of socio-religious life, it needs to be balanced with polite (moderate) Islamic teachings. Extremism, radicalism and terrorism are ideologies that are contrary to the views of society, so there needs to be a systematic effort to overcome them. Moreover, technological developments, especially in the digital space, are increasing rapidly. Therefore, this article seeks to explore the important contributions that Generation Z can make as productive consumers of social media to spread and implement religious moderation